2021
DOI: 10.3324/haematol.2020.260059
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-specific 2'-O-methoxyethyl antisense oligonucleotides activate human platelets through glycoprotein VI, triggering formation of platelet-leukocyte aggregates

Abstract: Antisense oligonucleotides (ASOs) are DNA-based, disease-modifying drugs. Clinical trials with 2'-O-methoxyethyl (2’MOE) ASOs have reported dose- and sequencespecific lowering of platelet counts according to two phenotypes. Phenotype 1 is a moderate (but not clinically severe) drop in platelet count. Phenotype 2 is rare, severe thrombocytopenia. This paper will focus on the underlying cause of the more common Phenotype 1, investigating the effects of ASOs on platelet production and platelet function. Five phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Accordingly, no increase in P-selectin surface expression was observed in vitro, and no specific PF4-ASO antibodies were detected in this study, suggesting that no direct platelet activation occurred and no induction of the HITlike humoral response developed in the study animals. The same sequence (ISIS104838) and other 2 MOE-modified and PS ASOs activated human platelets in vitro (release of alpha granule markers and P-selectin surface expression) through the GPVI binding mechanism [27]. On the other hand, a previous study in adult Göttingen minipigs treated with various LNA-based PS ASOs did not show a fall in platelet count following four weeks of treatment [29].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Accordingly, no increase in P-selectin surface expression was observed in vitro, and no specific PF4-ASO antibodies were detected in this study, suggesting that no direct platelet activation occurred and no induction of the HITlike humoral response developed in the study animals. The same sequence (ISIS104838) and other 2 MOE-modified and PS ASOs activated human platelets in vitro (release of alpha granule markers and P-selectin surface expression) through the GPVI binding mechanism [27]. On the other hand, a previous study in adult Göttingen minipigs treated with various LNA-based PS ASOs did not show a fall in platelet count following four weeks of treatment [29].…”
Section: Introductionmentioning
confidence: 93%
“…Due to the polyanionic nature of ASOs with PS backbone linkages, their nonspecific affinity to plasma and cellular surface proteins is enhanced [24][25][26]. Therefore, one mechanism by which platelets can be activated directly by ASOs is through nonspecific binding to platelet collagen receptor glycoprotein VI (GPVI), which then leads to platelet aggregation [22,27,28]. Moreover, ASOs can bind to platelet factor 4 (PF4), inducing a humoral response to the ASO-PF4 complex, similar to heparin-induced thrombocytopenia (HIT) [23,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thrombocytopenia, that is, decrease in platelet counts, has been occasionally reported in preclinical models (rodents and NHPs) and in three recent clinical trials following treatment with ONDs, in particular PS-ASO (volanesorsen, inotersen, and drisapersen) [ 84 ]. Two phenotypes of platelet count decrease have been distinguished: phenotype 1 characterized by a moderate but not clinically severe drop in platelet count and the rarer phenotype 2 of severe thrombocytopenia [ 85 ]. In contrast with PS-ASO, severe thrombocytopenia has not been reported for siRNA drugs, neither in preclinical studies nor in clinical trials, but encapsulation of siRNA in lipid nanoparticles has been shown to cause decrease in platelet counts in rats, presumably induced by the cationic lipid molecules themselves [ 86 , 87 ].…”
Section: Hybridization Independent But Sequence-dependent Toxicitiesmentioning
confidence: 99%
“…More recently, the sequence-specific binding of OND (PS-ASO specifically) to platelet glycoprotein VI was shown to activate human platelets triggering formation of platelet–leukocyte aggregates [ 85 ]. These findings also highlight the possibility of a genetic susceptibility component given that donors with higher platelet glycoprotein VI levels had greater OND-induced platelet activation.…”
Section: Hybridization Independent But Sequence-dependent Toxicitiesmentioning
confidence: 99%